Human behavior understanding : 7th International Workshop, HBU 2016, Amsterdam, the Netherlands, October 16, 2016, Proceedings /: 7th International Workshop, HBU 2016, Amsterdam, the Netherlands, October 16, 2016, Proceedings. (2016) - Unknown
No abstract available